A LEGISLATION ON ANTI-DISCRIMINATION IN THE PROTECTION OF HUMAN RIGHTS IN SOUTHEAST EUROPE - Filipovski, Zoran (International Scientific Journal Vision, 2019)
Anti-discrimination, ie, legislation to combat discrimination is an integral part of the legislation of the countries of Southeast Europe, especially in the countries of the Western Balkans. The integration processes of these countries are foundation for reforms in the rule of law, including the fight against discrimination. In this context, reforms undertaken in chapters 23 and 19, ie the judiciary and fundamental rights and employment and social issues, are aimed at harmonizing the laws of these countries with the EU legislation, which only suggests that legal protection against discrimination on gender, nationality, religion, sexual orientation or political affiliation is guaranteed by national laws in the countries of Southeastern Europe. In this scientific work will be presented the situation of human rights and freedoms in the countries of southeastern Europe, with a particular aspect of the cases relating to discrimination based on sex, religion, sexual orientation, with particular reference to political cases against discrimination, which is growing in the last period in this region. It will also be elaborated situations in which people who are victims of discrimination, because of lack of awareness about these social issues, rarely fail to complete the complex procedure of infringement granted to legal protection. Through the comparative analysis of the legislation of these countries with the legislation of the European Union, the reasons and factors wich prevent access to justice for victims of discrimination will be clarified.